Transformasi Sosial Perempuan Kepala Keluarga melalui Program PEKKA - Subasman, Iman; Fikriyan, Zaka; Aliyyah, Rusi Rusmiati; Saptarini, Any (Penerbit Goodwood, 2023)
Purpose: The Women-Headed Household Empowerment Programme (PEKKA) aims to improve the welfare and economic independence of women headed households through improved skills and market access. Methodology: This study was conducted using a participatory action research approach in a community of women headed family. The methods used included practical training in product packaging and digital marketing strategies, particularly the use of social media. The study also adopted surveys and interviews to collect data. Results/Findings: Results showed significant improvements in the ability of female-headed households to produce and market products, leading to increased income. Social impacts noted included a reduction in school dropout rates and unemployment among the families involved. Limitations: The study was limited to a specific region, so the results may not be directly applicable to different contexts without customisation. Contribution: The findings provide important insights for policymakers and community development practitioners in designing economic empowerment programmes focused on female-headed households, with potential application in other regions.